2005
DOI: 10.1165/rcmb.2004-0365oc
|View full text |Cite
|
Sign up to set email alerts
|

Lung Surfactant Gelation Induced by Epithelial Cells Exposed to Air Pollution or Oxidative Stress

Abstract: Lung surfactant lowers surface tension and adjusts interfacial rheology to facilitate breathing. A novel instrument, the interfacial stress rheometer (ISR), uses an oscillating magnetic needle to measure the shear viscosity and elasticity of a surfactant monolayer at the air-water interface. The ISR reveals that calf lung surfactant, Infasurf, exhibits remarkable fluidity, even when exposed to air pollution residual oil fly ash (ROFA), hydrogen peroxide (H 2 O 2 ), or conditioned media from resting A549 alveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 41 publications
(61 reference statements)
3
51
0
Order By: Relevance
“…As evidenced by the elevation of 8-hydroxydeoxyguanosine in the BALF from the 9,10-PQtreated rats, the accumulation of the abnormal surfactant observed during quinone exposure is possibly attributable to an enhanced level of ROS. The formation of the abnormal surfactant might also be explained by the findings that ROS modify the surfactant components and consequently cause the formation of conjugated dienes and protein carbonyls and SPA dysfunction (Andersson et al 1999) and that the chronic exposure of lung cells or of rats to DEP and ROS induces surfactant gelation and compositional changes in lipid components (Eskelson et al 1987;Anseth et al 2005). Thus, the unusual metabolism of the surfactant evoked by 9,10-PQ probably results from oxidative modifications of components by ROS; this is suggested to be a novel mechanism of alveolopathy caused by DEP inhalation.…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced by the elevation of 8-hydroxydeoxyguanosine in the BALF from the 9,10-PQtreated rats, the accumulation of the abnormal surfactant observed during quinone exposure is possibly attributable to an enhanced level of ROS. The formation of the abnormal surfactant might also be explained by the findings that ROS modify the surfactant components and consequently cause the formation of conjugated dienes and protein carbonyls and SPA dysfunction (Andersson et al 1999) and that the chronic exposure of lung cells or of rats to DEP and ROS induces surfactant gelation and compositional changes in lipid components (Eskelson et al 1987;Anseth et al 2005). Thus, the unusual metabolism of the surfactant evoked by 9,10-PQ probably results from oxidative modifications of components by ROS; this is suggested to be a novel mechanism of alveolopathy caused by DEP inhalation.…”
Section: Discussionmentioning
confidence: 99%
“…In general, a trend was observed that cultures with a low thiol concentration contained the most MII cells and necrotic cells. H 2 O 2 incubations have been used [10][11][12][13]15]; this prompted the current authors to perform a detailed time-dependent dose-response study and to define limits for in vitro resistance and recovery. For this purpose, cells were challenged with H 2 O 2 at concentrations above levels implicated in cell signalling (50 mM) [23] but below levels that would lead to cell death within minutes (10 mM).…”
Section: Resistance Of Airway Epithelial Cells To H 2 O 2 Mp Smit-dmentioning
confidence: 99%
“…For this purpose, cells were challenged with H 2 O 2 at concentrations above levels implicated in cell signalling (50 mM) [23] but below levels that would lead to cell death within minutes (10 mM). In most described cases, A549 cells are maintained in medium containing serum up to the moment the experiment starts [11,12,15]. When the cultures are not 100% confluent it is likely that they are still proliferating at the start of the experiment.…”
Section: Resistance Of Airway Epithelial Cells To H 2 O 2 Mp Smit-dmentioning
confidence: 99%
See 2 more Smart Citations